Projeto de um manipulador robótico com extremidade do tipo garra acionado por FPGA - Machado, Menotti Erasmo da Silva (2010)
This work focuses on the design and control of a robotic manipulator using FPGA (Field Programmable Gate Array) circuits. Three open-loop control strategies were developed to move the manipulator, through the activation of three bipolar stepper motors. The first strategy considers a manual control; the second one consists of a numerical control, and the third one uses fixed sequence control inputs. The manipulator structure is organized in three main parts: base, arm and claw. Each one of them with a stepper motor connected, making possible pitch and/or yaw movements. The manipulator is mechanically constituted by rotational and torsional joints, and its work space corresponds to a semi-spherical surface. The programming and simulation of the logical expressions used in the control algorithms were coded in VHDL (VHSIC Hardware Description Language), using the Altera Quartus II software. The generated code was synthesized on Cyclone II FPGA, which is part of the Altera DE2 development kit. The computer simulation results showed that digital control circuits correctly perform the scheduled tasks for all three tested control strategies. The developed robotic arm is able to execute three different and complementary movements: roll motion in the base, another to alight the arm that holds the claw, and a third to open or close it. It is remarkable that the flexibility obtained by the use of FPGA devices allows modifications of control strategies without the need of interrupting the operation of the implemented robotic system, which is a desirable feature in an industrial environment. The prototype can be used in environments where the task to be performed poses risks to human health, such as handling toxic and/or radioactive materials.